2000
DOI: 10.1021/bi000975w
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative Mechanism of Thermal Denaturation of Rabbit Skeletal Muscle Glycogen Phosphorylase b

Abstract: The thermal stability of rabbit skeletal muscle glycogen phosphorylase b was characterized using enzymological inactivation studies, differential scanning calorimetry, and analytical ultracentrifugation. The results suggest that denaturation proceeds by the dissociative mechanism, i.e., it includes the step of reversible dissociation of the active dimer into inactive monomers and the following step of irreversible denaturation of the monomer. It was shown that glucose 1-phosphate (substrate), glucose (competit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 20 publications
5
28
0
Order By: Relevance
“…The sedimentation coefficients were corrected to solvent density and viscosity (208C, water) in the standard way as described earlier. 14 …”
Section: Analytical Ultracentrifugationmentioning
confidence: 99%
See 1 more Smart Citation
“…The sedimentation coefficients were corrected to solvent density and viscosity (208C, water) in the standard way as described earlier. 14 …”
Section: Analytical Ultracentrifugationmentioning
confidence: 99%
“…There is a lag period on the kinetic curve. To explain the appearance of the lag period, we proposed the kinetic scheme 14 including the stage of the conformational transition in the dimeric form of Phb. The theory of the lag periods for thermoinactivation of oligomeric enzymes that allows the number of the conformational transitions preceding the stage of irreversible denaturation to be determined was elaborated by Bednarck et al 32 The fact that the inactivation rate increases with decreasing Phb concentration means that the stage of irreversible denaturation of monomers is preceded by the stage of reversible dissociation of dimer into monomers.…”
Section: Effect Of A-crystallin On Thermal Inactivation Of Phbmentioning
confidence: 99%
“…Our experiments showed that in LSAO, T m and ÁH of the DSC profile are independent of the protein concentration. Based on reports of Takahashi and Sturtevant 18) and Kurganov et al 19) The independence of thermal parameters from protein concentration shows that oligomerization does not contribute to the thermal unfolding process. So in the thermal denaturation of LSAO dissociation to monomers does not play any role.…”
Section: Discussionmentioning
confidence: 94%
“…The Phb molecule consists of two identical subunits with molecular masses of 97.4 kDa each. The data on analytical ultracentrifugation provide evidence of the dissociation of the dimer into monomers at elevated temperatures Kurganov et al 2000;Meremyanin et al 2008). …”
Section: Dissociative Mechanism For Irreversible Thermal Denaturationmentioning
confidence: 99%
“…1 Kinetics of thermal inactivation of Phb from rabbit skeletal muscles at 53°C (0.08 M Hepes-NaOH, pH 6.8). The relative enzymatic activity A/A 0 versus time plot was constructed on the basis of the data represented in the work by Kurganov et al (2000). Enzyme concentration: 1 1.6 and 2 5.2 mg/mL function of protein concentration has the following form (Kurganov 1966):…”
Section: Dissociative Mechanism For Irreversible Thermal Denaturationmentioning
confidence: 99%